Drivers and barriers of logistics capabilities outsourcing to South African SMMEs by multinational retailers during their internationalisation stages - Waugh, Beverley (University of Pretoria, 2023)
Mini Dissertation (MPhil (International Business))--University of Pretoria, 2022.